Laporan Kasus: Usia Lebih dari 40 Tahun sebagai Faktor Risiko Mola Hidatidosa - Nasution, Rizqiani Astrid; Algifari, Muhammad Zaidan; Zulfadli, Zulfadli (Medula, 2024)
Hydatidiform mole is a type of abnormal pregnancy in which the fetus does not develop and almost all of the chorial villi undergo hydropic changes or degeneration that resemble grapes or fish eyes. The incidence of hydatidiform mole is higher in Asian, African, and Latin American countries compared with Western countries. In Indonesia, the incidence of hydatidiform mole is 1 in 85 pregnancies. This condition is caused by abnormal chromosomal fertilization. A diagnosis of hydatidiform mole can be made if the following signs are found: amenorrhea, vaginal bleeding, uterine size larger than expected for gestational age, no signs of pregnancy, beta-hCG levels that are higher than normal, and a vesicular appearance in the uterine cavity. on ultrasound examination. The most accurate diagnosis is when a molar bubble is found. In the first trimester, molar appearance is usually less specific than in the second trimester, where the appearance becomes more typical. In the second trimester, it can be seen that the uterine cavity contains an echogenic mass mixed with anechoic vesicular parts with a diameter of 5-10 mm or looks like a honeycomb. Risk factors that increase the prevalence of molar pregnancy include extreme maternal age (age >40 years has a five to ten-fold increased risk) and early adolescence (usually <20 years), a history of previous molar pregnancy increases the risk by 1%-2% for subsequent pregnancies, women who have had a spontaneous abortion or infertility, dietary factors include patients who have a diet deficient in carotene (a precursor of vitamin A) and animal fats, and smoking. In this case, the risk factor for hydatidiform mole was the patient's age.